الإسهام النسبي لتوجهات الهدف في التنبؤ بفاعلية الذات لدى المراهقين - هلال، محمد عبدالمنعم محمد محمد; عيسى، لطفي عبدالباسط إبراهيم; محمد، محمد عبدالرءوف عبد ربه (جامعة المنوفية - كلية التربية, 2021)
يهدف البحث إلى فحص العلاقة الارتباطية بين توجهات الهدف وفاعلية الذات وفقا للتصنيف السداسي لتوجهات الهدف، وكذلك التعرف على الإسهام النسبي لمكونات توجهات الهدف الستة في التنبؤ بفاعلية الذات لدى المراهقين، وذلك لدى عينة تكونت من ‎١٨٢ (‏ 73 ذكور، ‎109 ‏إناث) من المراهقين والمراهقات من طلبة الصف الثالث الإعدادي، وباستخدام مقياس توجهات الهدف إعداد حجاج غانم أحمد (2015)، ومقياس فاعلية الذات إعداد نهى محمد شعث ‎(٢٠١٤)‏ ‏أظهرت نتائج الدراسة: (١)‏ وجود علاقات إرتباطية موجبة دالة إحصائيا عند مستوى(0.01)‏ بين الأبعاد الفرعية (أهداف الإقدام المعتمدة على المهمة، أهداف الإقدام المعتمدة على الآخرين، أهداف الإقدام المعتمدة على الذات، أهداف الإحجام المعتمدة على المهمة، أهداف الإحجام المعتمدة على الآخرين، أهداف الإحجام المعتمدة على الذات) مع معظم الأبعاد الفرعية والدرجة الكلية لمقياس فاعلية الذات، (٢) ‏أظهر نموذج تحليل الانحدار أن المتغيرات (أهداف الإقدام المعتمدة على الذات، أهداف الإقدام المعتمدة على المهمة، أهداف الإقدام المعتمدة على الآخرين، أهداف الأحجام المعتمدة على الذات) تسهم معا إيجابيا بنسبة (60.8) % من التباين في فاعلية الذات. This study aims of the research is to examine the correlation between goal orientations and self-efficacy according to the hexagonal classification of goal orientations, as well as to identify the relative contribution of the components of the six goal orientations in predicting self-efficacy among adolescents, in a sample of adolescents. It consisted of 182 (73 males, 109 females) male and female adolescents from the third preparatory grade students, and using the goal orientation scale prepared by Hajjaj Ghanem Ahmed (2015), and the self-efficacy scale prepared by Noha Muhammad Shaath (2014), the results of the study showed: (1) There are Statistically significant positive correlations at the level (0.01) between the sub-dimensions (task-dependent audacity goals, others-dependent audacity goals, self-dependent audacity goals, task-dependent reluctance goals, others-dependent goals, self-dependent aversion goals) with most of the sub-dimensions and the total score of the measure of self-efficacy, (2) The regression analysis model showed that the variables (self-reliant audacity goals, task-based audacity goals, others-dependent audacity goals, and self- reliant volume goals) together contribute positively by (60.8%) of the variance in self-efficacy.
Keywords: الصحة النفسية -- التنبؤ الإجتماعي -- المراهقين -- علم النفس التربوي